Technical Assistance Evaluation Program : Findings of Evaluations and Updated Program. (Policy Papers; Policy Paper, 2006)
This paper is the third to be issued under the Fund's Technical Assistance Evaluation Program, which was launched in FY 2003. It reports on the findings of five completed evaluations, and updates the program of evaluations for FY 2007-2009. The completed evaluations featured in this paper are: (i) an evaluation of technical assistance provided by the Legal Department to Indonesia related to the strengthening of the commercial courts and the implementation of the bankruptcy law; and (ii) evaluations of technical assistance delivered by the Monetary and Financial Systems Department to Sierra Leone, the Democratic Republic of the Congo, Bosnia and Herzegovina, and Kosovo to strengthen capacity in the financial sector.